KONSEP NAFKAH MENURUT YUSUF QORDHOWI DALAM KELUARGA POLIGAMI (Studi Kasus Di Desa Badas Kecamatan Sumobito Kabupaten Jombang) - Siti Hajar Putri Aristya; Abd. Aziz (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2019)
This research is driven by a paradigm that sharia or islamic law obligates the man as the husband to earn and give livelihood fot the wife. However Al-Qur’an and Hadis never firmly assert the measurement of thr livelihood in the minimal and maximal convention. As tjhr fotmulaton of the problem, the researcher is going to discuss about Yusur Qardhawi’s opinion related to livelihood fot the wife in Hadyu al-Islam Fatawa Mu’ashiroh. It’s going to explore how the implementation of yusuf Qardhawi’s point towards the reality that happens in the polygamic family in Badas Sumobito Jombang. This research is usig drscriptive research which discriber and represents the reality in field. It is analyzed withal the theory of contemporary theologians. The primary data, Hadyu al-Islam Fatawa Muashiroh book, is composed by yusuf Qardhawi with intervewin some related speakers. The scondary data is coming from some relevant books to the paper’s title. The submission of data applies documentary method while descriptive analysis is implemented as the method of data analysis.